Refugees, migrants and stateless persons in international law - Tomasz Słapczyński (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
In the paper the author attempts to describe the issue of refugees as a very important problem in international law, a problem which generates profits e.g. a rise in human capital, as well as losses e.g. costs, for the countries involved. The balance depends on the policy of a given country, whether this country is able to capitalize on the human capital or whether it is only counting costs. Sometimes obligations resulting from international law are not sufficient to convince societies that accepting refugees is the right decision. The paper will focus on how, with appropriate legislative tools, the united world can help people who are in danger. The author will also pose a question whether enough is being done, or whether the scope and methods currently in use should be amended. The paper discusses the issue of refugees from the perspective of various organizations involved i.e. global institutions like UNHCR, European Union institutions, non-government organizations (NGOs) and contains a review of relevant legal acts such as the Treaty of Lisbon, the Geneva Convention etc. The author also touches upon the practical side of the refugee policy execution in various countries.